Ethics in the market place: a Jewish perspective - Raḳover, Naḥum (The Library of Jewish Law, 2000)
Machine generated contents note: Chapter One FRAUDULENT PRICING 19 --Chapter Two DEFECTIVE WEIGHTS AND MEASURES 27 --Chapter Three MISREPRESENTATION AND FRAUD 31 --Chapter Four PROFITEERING BY HOARDING AND WITHHOLDING SALE 39 --Chapter Five PRICE CONTROL AND CONSUMER BOYCOTTS 47 --Chapter Six RESTRICTION OF RESALE OF ESSENTIAL GOODS 71 --Chapter Seven SUPERVISION AND PENALTIES 75 --Chapter Eight CONCLUSION 81 -- Part Two --MARKET OVERT -- Purchase of Stolen Goods Introduction 91 --Chapter One BACKGROUND AND TRENDS 93 -- Chapter Two THE MAIN PRINCIPLES OF THE ENACTMENT 103